Impacto de fatores intrínsecos e extrínsecos sobre o desenvolvimento de lactentes prematuros e a termo - Santos, Mariana Martins dos (Universidade Federal de São Carlos, 2017)
BACKGROUND: Walking acquisition is one of the most important milestones during the first year of life that involves changes in spatial perception, cognition and emotional development. The acquisition and improvement of gait are influenced by intrinsic and extrinsic factors. Prematurity is an intrinsic risk factor for child development, even when infants are classified as moderate and late preterm, due to vulnerability in many body systems, especially in the Central Nervous System. Studies report that preterm infants present poorer motor and cognitive performance and quality of walking movements when compared to full-term infants. However, little is known about how intrinsic and extrinsic factors interfere in this process. OBJECTIVE: To investigate how intrinsic and extrinsic factors influence the motor, cognitive, sensory development and walking characteristics METHODOS: 34 preterm infants (mean corrected age of 15.6) and 34 term infants (mean age of 13.7 months) were enrolled in the children development evaluation and 10 preterm infants (mean corrected age of 16.8) and 16 term infants (mean age 15.4 months) participated performed the gait analysis. Information about birth and socioeconomic conditions was collected through a questionnaire. Motor, cognitive and language performance was assessed with the Bayley Scale of Infant Development-3rd Edition scale, the Sensory Profile was applied through an interview with mothers for evaluation of sensory modulation. The Home Observation for Measure of the Environment Inventory was used to evaluate the care quality and kinematic gait evaluation used the Qualisys ProReflex MCU motion analysis system. For comparison between groups T-test was used for parametric data, Mann Whitney test for the non-parametric data and Chi Square for the categorical variables. In addition, Spearman and Pearson tests were performed for correlation according to data distribution. RESULTS: A gap has been identified in the literature regarding the impact of intrinsic and extrinsic factors on the gait acquisition and refinement process. Preterm infants presented lower motor and cognitive performance than term infants. The quality of care of preterm infants also presented lower scores, with lower family income and maternal education. Lower gestational ages were related to lower motor and cognitive performance. Higher degrees of maternal education and higher family income were associated with higher motor, cognitive and language performances. Lower scores on quality of care were associated with lower cognitive and language performances and higher scores on the aversive and spectator quadrants. The premature group presented similar gait characteristics as the term group, except for hip angulation, that was higher in the preterm group. Factors such as age of acquisition, time of walking experience, gestational age, height at birth and APGAR in the first and fifth minutes, home environment and maternal and paternal education are related to several gait characteristics. CONCLUSIONS: Moderate and late prematurity cause lower motor and cognitive performances and more immature gait in comparison to term infants. Intrinsic (gestational age, weight) and extrinsic factors (quality of care, family income and maternal and paternal education) were shown to influence motor, cognitive and language development, sensory modulation and gait characteristics. Moderate and late preterm infants require a carefully follow-up during first two years, even if there are no clear signs of dysfunction.
Keywords: Prematuro; Marcha; Desenvolvimento infantil; Modulação sensorial; Infant; Preterm; Child development; Sensory modulation; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL